KORELASI KETERAMPILAN MEMAHAMI TEKS LAPORAN HASIL OBSERVASI DAN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI - Yulianti Yulianti; Erizal Gani; Tressyalina Tressyalina (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this study is to (1) describe the skills to understand the text of the observation report, (2) to describe the skills of writing the text of the observation report, and (3) to describe the correlation of the skill in understanding the text of the observation report and the writing skill of the observation report of the seventh grade students of SMP Negeri 31 Padang. The data in this research is the score of comprehension skills and the score of writing skill of the observation report. The source of this research data is the seventh grade students of SMP Negeri 31 Padang, amounting to 40 people. Data were collected using descriptive method. The findings of this research is the correlation between the comprehension of the text of the observation report and the skills of writing the text of the observation result of the students of class VII of SMP Negeri 31 Padang. Kata kunci: korelasi, teks, keterampilan, memahami, menulis